PENDIDIKAN KARAKTER DI MADRASAH SALAFIYAH - Sa’adah, Fihris (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
Theoretically, one of the dominant factors that influence the development of individual character are environmental factors which is a condition that allows the process of personal character development. Creating an conducive environment to the development of character Girikusumo Salaf Islamic School students is done by creating a tradition /habituation practical in everyday life in all their daily activities in relation to the quality of their religious or otherwise. Attempt the formation of character through this Salaf Islamic school in addition to the above character education, can also be done simultaneously through the educational value of the following steps. First, apply a “modeling” or “exemplary” or “uswah hasanah”. Second, efforts to explain or clarify to students constantly about the value of good and evil has been done in the Girikusumo Salaf Islamic School. Third, implement the SIS is based on character education.***Secara teoritik, salah satu faktor dominan yang mempengaruhi perkembangan karakter individu adalah faktor-faktor lingkungan yang merupakan kondisi yang memungkinkan proses perkembangan karakter pribadi. Menciptakan lingkungan yang kondusif bagi perkembangan karakter di kalangan siswa Sekolah Islam Salaf Girikusumo dilakukan dengan cara menciptakan tradisi atau praktek pembiasaan dalam kehidupan sehari-hari yang terkait dengan peningkatan kualitas keagamaan atau kehidupan mereka. Di samping upaya di atas, pembentukan karakter juga dilakukan dengan simultan melalui penanaman nilai dengan langkah-langkah sebagai berikut: pertama, menerapkan pencontohan atau uswah hasanah. Kedua menjelaskan tentang nilai yang baik dan buruk. Ketiga, mengimplementasikan SIS yang didasarkan pada pendidikan karakter.